Princess Jellyfish. 07 - Higashimura, Akiko (Kodansha Comics, 2017)
"In order to save Amamizukan, Tsukimi makes the ultimate sacrifice: she goes to Singapore to work as a designer for Kais fashion company. While Amars seems to accept Tsukimis departure and the end of Jelly Fish, Kuranosuke refuses to give her up without a fight! As she floats further and further away from home, Tsukimi struggles to learn the ins and outs of the fashion industry, as well as decipher the motives of the enigmatic Kai"--Page [4] of cover.